Transfer film formation mechanism and tribochemistry evolution of a low-wear polyimide/mesoporous silica nanocomposite in dry sliding against bearing steel - Ma, J.; Qi, X.; Dong, Yu; Zhao, Y.; Zhang, Q.; Fan, B.; Yang, Y. (Pergamon, 2018)
The addition of a kind of mesoporous silica (MPS) can significantly reduce the wear rate of a thermoplastic polyimide (PI) by more than 90%, which is ascribed to the quick formation of high-quality transfer films induced by unique tribochemical reactions [1]. In-situ observation illustrated the morphology evolution of the transfer films. Further X-ray photoelectron spectroscopy on these transfer films revealed the variation of tribochemical reactions intensity while significant tribochemically induced polymer decomposition and reactions was detected by infrared spectroscopy. Intact and robust transfer films were formed by initial tribochemical adhesion of wear debris and its subsequent accumulation and expansion on the steel surface, which was ascribed to the combined effects of tribochemistry and reduced size and varied morphology of the wear debris.